Optical sensors for bond-slip characterization and monitoring of RC structures - Mesquita, Esequiel (2018)
Bond-slip is an important interaction between steel and concrete in reinforced concrete (RC) structures and other civil engineering constructions. It is essential to understand and to characterize, at local level, this stress transference mechanism. In particular its behavior for monotonic and cyclic demands, the parameters that influence this mechanism, and how it is affected by different deterioration factors. Therefore, characterizing and monitoring the bond-slip mechanism is essential for the safety assessment of RC structures, more specifically determining the reinforcing bars slippage inside the concrete, and therefore the stress and strain distribution in RC members. In this work, two optical fiber sensors are presented, based on silica and polymer fiber Bragg gratings (FBGs), which were implanted inside a concrete block specimen and subjected to a pull-out test. After 6 days of curing, the pull-out test was recorded and the displacement incurred during the test was also monitored with a traditional electric sensor; for comparison with the data acquired with the two optical sensors. The results obtained confirm the viability and advantages of the optical sensors, evidenced by their higher resolution and far lower dimensions (allowing them to be embedded into the concrete) when compared with their electronic counterparts. The straightforward implementation and use of the optical sensors show very promising results when used in civil engineering structures.